(untitled) (Applied Biological Research, 2024)
The medicinal properties of plants have been known for centuries, making them an invaluable resource for the people in need of treatment. Humans on every continent have long relied on the healing properties of plants, a practice that may be traced back to prehistoric times. Melaleuca citrina is a plant with substantial therapeutic potential. To the best of our knowledge, no published work has characterized the chemical composition of M. citrina in Nigeria. This study aimed to analyse the bioactive chemical constituents of essential oil extracted from the leaves of M. citrina in Nigeria. A Clevenger style apparatus was used to hydro-distillate the freshly chopped leaves of M. citrina for a duration of two to three hours. After the extraction process, the essential oils were separated and dried using anhydrous sodium sulphate. Then, the oil composition was examined using gas chromatography-mass spectrometry. Here are the main compounds: (-) Spothulenol 8.6%, Cryptomeridiol 5.5%, Selinene gamma 8%, Pinocarveol cis-> 15%, Cymene para 10%, Selinene delta 10%, and globulol 27.3%. Astringent, antibacterial, anti-inflammatory, and antiseptic are just a few of the fascinating biological characteristics exhibited by globulol, the main component of essential oils. Essential oils extracted from the leaves of Melaleuca citrina possess strong natural qualities that can work as anti-inflammatory, antibacterial, antiseptic, and astringent agents.